Affirmative action and the question of general category in India: judicial treatment of constitutional, legislative, and executive interventions in determining backwardness and intra-classification challenges - Wankhede, A (2021)
The proliferation of reservations based on persistent demands of upper-castes or advantaged groups has given rise to a complex set of recurrent legislative interventions in India. 2019-Amendment provision of quota benefits to EWS or socially advantaged sections based on economic disadvantage marks a crucial shift in the constitutional policy of reservations. This thesis critically engages with the constitutional and state legislative reservations policies, and their judicial treatment, for EWS and upper-castes in Maharashtra, Gujarat, and Haryana. The thesis is divided into three chapters. The first chapter undertakes an analysis of the legislative and judicial history of Indian interventions and outlines the political economy behind them. The second chapter critically analyses the judgements challenging the constitutionality of the 2019-Amendment and state measures. Chapter 3 carries out an analysis of major problems and themes inductively identified and evaluates how discrimination law theory best explains the implications of the post-2019 regime on Indian affirmative action and multi-dimensional substantive equality. It is argued that reservations for upper-castes are not affirmative action measures and substantive equality. They amount to collateral discrimination as they burden cognate groups with quotas not meant for reducing relative group disadvantage. They are also discriminatory towards existing status groups. The de facto nature of EWS is of ‘upper-caste Hindu men’ which misses addressing intersectional poverty discrimination. As a key implication, the commitment of the Constitution towards substantive equality stands diluted and symbolised by enabling advantaged groups access to quotas historically devised for protected groups. The distinction between historical discrimination-based reservations and general poverty alleviation measures has collapsed giving rise to accommodating all positions of injustices under reservations. In the long-term, such developments may lead to withering-down and may displace historical discrimination-foundation for reservation policy to a general system of communal quotas for all castes and classes based on income poverty ground.